Prospecção geofísica entre as ocorrências cupríferas Capão Grande e Victor Teixeira, Caçapava do Sul - RS - Pereira, Henrique Garcia [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This paper consists of the acquisition of terrestrial magnetometry data in an area comprised of two mineralized occurrences copper called Capão Grande and Victor Teixeira, located in the city of Caçapava do Sul, in the south of Brasil. The resulting data from the application of this geophysical method characterizing the subsurface to check a potential connection relationship between these copper mineralization occurrences. The Capão Grande occurrence has the enclosing sedimentary rocks of the Camaquã Basin. Victor Teixeira occurrence is inserted into metamorphic rocks Sul-Rio-Grandense Shield. In characterizing subsurface magnetic surveys were employed intensity of the total magnetic filed measurements along the profiles and in the form of mesh in the of 2300 m between the mineralized occurrences. These measurements were processed together, and the products resulting were, the total field maps, band pass deep, band pass shallow, and the analytic signal amplitud. Analysis and further discussion of these maps with the overlay of the main geological information of the area and geophysical results of interest from previous studies allowed the definition of the mineralization of the cases studied show no connection in the subsurface

Esse trabalho consiste na aquisição de dados de magnetometria terrestre numa área compreendida por duas ocorrências cupríferas denominadas Capão Grande e Victor Teixeira, localizadas no interior do município de Caçapava do Sul-RS. Os dados resultantes da aplicação desse método geofísico foram adquiridos com o propósito de caracterizar a subsuperfície para verificar uma potencial relação de conexão entre as mineralizações dessas ocorrências de cobre. A ocorrência Capão Grande tem como encaixante as rochas sedimentares da Bacia do Camaquã. Já a ocorrência Victor Teixeira está inserida em rochas metamórficas do Escudo Sul-Rio- Grandense. Na caracterização de subsuperfície foram empregados levantamentos de medidas de intensidade do campo magnético total ao longo de perfis e sob a forma de malha no intervalo de 2300 m entre as ocorrências mineralizadas. Essas medidas foram processadas em conjunto, e os produtos resultantes foram os mapas do campo magnético total, passa banda profundo, passa banda raso e amplitude do sinal analítico. Análises e discussões posteriores desses mapas com a sobreposição das principais informações geológicas da área e de resultados geofísicos de interesse de estudos anteriores permitiram a definição de que as mineralizações das ocorrências estudadas não apresentam conexão em subsuperfície
Keywords: Magnetometry; Geofisica; Magnetometria; Prospecção mineral; Caçapava do Sul (RS)